A correlation of the spirometric outcomes of follow up patients of COVID-19 pneumonia with their admission time computed tomography severity score on high resolution computed tomography thorax - Patra, Sucharita; Khyalappa, Rajesh (International Journal of Research in Medical Sciences, 2023)
Background: Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Most people who fall sick with COVID-19 experience mild to moderate symptoms and recover without any special treatment. However, some become seriously ill and require serious medical attention. The respiratory system has been the main organ affected by COVID-19 along with other organs such as heart, kidneys and liver. Spirometry is the most common of the pulmonary function tests. Spirometry is helpful in assessing respiratory outcomes that identify conditions such as asthma, pulmonary fibrosis, cystic fibrosis, and COPD. Methods: A total of 100 COVID-19 pneumonia patients coming for follow-up 6-10 weeks post-discharge in OPD at Department of General Medicine, Dr. D. Y. Patil Medical College Hospital and Research Institute, Kolhapur, Maharashtra, satisfying the inclusion criteria and exclusion criteria were enrolled. High resolution computed tomography (HRCT) thorax reports during their admission were collected and Computed tomography severity score (CTSS) was noted. Their spirometry was done and pattern of spirometric outcome noted. Admission-time CTSS and spirometric outcome were correlated. Results: In majority of the patients, CT severity score during course of illness had strong correlation with spirometric outcome after 6 weeks of follow up and the association was statistically significant. Conclusions: CT severity score during course of illness had strong correlation with spirometry findings after 6 weeks of follow up. Higher age and higher HRCT score are good predictors for impaired pulmonary function after discharge.